Jurnal Management Informatika Implementasi Scrum Master Pada Perangkat Lunak - Sofyan Mufti Prasetiyo; Andri Abdul Aziz; Vierly Unggul Buntoro; Yoga Hilmawan (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Scrum is one component of the Agile development methodology regarding daily meetings to discuss progress. Scrum began when Jeff Sutherland's men who worked at Easel Corporation read Professor Takeuchi Tanaka's article published in the Harvard Business Review on project management in 1993. Scrum has been adopted by many managers who want to ensure that they produce the best possible product and by developers. who want to ensure that they can do their jobs to the best of their ability. Secrum uses an approach to use the data found from this inspection and adaptation process as learning material in order to find a way out.